Analysis of anxiety and depression phenomena in the first weeks of the war: gender and age aspects - Yuryeva Людмила; Vyshnichenko Сергій; Shornikov Андрій (Psychosomatic Medicine and General Practice, 2022)
Background. There is a high prevalence of psychogenic disorders, in particular depressive and anxiety, in people who have been exposed to extreme intensity of traumatic influences. However, there is no data on depression and / or anxiety in the first weeks of the war. The aim of the study was to assess the prevalence of anxiety and depression, as well as to identify risk factors for the development of these conditions in individuals during the first weeks of the war. Methods. A cross-sectional epidemiological study involving 140 respondents who voluntarily and anonymously have completed a questionnaire with complaints, anamnestic data, and a self-assessment scale for depression PHQ-9 and anxiety GAD-7 was performed. Results. The mean severity of anxiety was 8.0 (4.5; 12.5) points. The prevalence of anxiety on the GAD-7 test with an accuracy cut-off of 4 points was 75% (105/140) of respondents, with an accuracy cut-off of 10 points - 37.86% (53/140) of respondents. The mean severity of depression was 8.5 (5.0; 12.5) points. The prevalence of depression on the test PHQ-9 with an accuracy cut-off of 4 points was 76.4% (107/140) of respondents, with an accuracy cut-off of 10 points - 42.5% (60/140) respondents. The study found no statistically significant differences in gender, age, employment, complaints, chronic diseases, COVID-19 and its vaccination. Conclusions. The prevalence of anxiety and depression in the first weeks of the war was high. The most significant risk factors for anxiety and depression are the number of complaints, the presence of depression / anxiety respectively, and subjectively reduced work capacity. Past COVID-19 and / or vaccination against it have not affected the occurrence of depression and anxiety.